STRATEGI RECOVERY PENGEMBANGAN DESA WISATA KANDRI DI KECAMATAN GUNUNGPATI PASCA PANDEMI COVID-19 - Chasanah, Lailatul; Rostyaningsih, Dewi; Sunu Astuti, Retno (Journal of Public Policy and Management Review, 2024)
Kandri Tourism Village, Semarang City has the potential to become a leading tourist destination. However, during the COVID-19 pandemic, visits decreased and the sustainability of natural resources was threatened. This research aims to analyze the strengths, weaknesses, opportunities, challenges and development strategies of the Kandri Tourism Village in Gunungpati District. The qualitative research approach uses observation, interviews, documentation, and literature study as data collection techniques. SWOT Analysis and Litmus Test are used as data analysis tools. Research findings show that the strength of the Kandri Tourism Village lies in its agricultural appeal which attracts visitors who are interested in the lives of local communities. However, weaknesses such as the absence of a dedicated souvenir shop and lack of parking spaces were identified. Opportunities include strong support from government and the community, as well as the potential to improve visitor services. The main threat identified is limited human resources for village management and development. The recommended strategy involves collaborating with the private sector or government entities to improve facilities and infrastructure that currently hinder development.